YUGOSLAVIA-INDIA DIPLOMATIC RELATIONS IN THE 1950s - ТЕРЗИЋ, Предраг Р.; Anchev, Stefan (Serbian political thought, 2025)
The origins of Yugoslav–Indian relations may be traced to the very inception of India’s independence. Although diplomatic relations were officially established on December 5, 1948, India did not accredit an ambassador to Yugoslavia until 1954. During the years 1950 and 1951, Yugoslavia, India, and Ecuador held non-permanent seats on the United Nations Security Council, and throughout this period, Yugoslavia and India consistently adopted aligned positions on a broad spectrum of international political matters, thereby laying a firm foundation for the subsequent deepening of their bilateral political engagement. The Non-Aligned Policy in Yugoslavia emerged due to the lack of cooperation with Western countries, but also due to the 1948 Cominform Resolution, which marked the breakdown of relations with the Soviet Union and other Eastern Bloc countries. In establishing the principles that Yugoslavia applied when defining its foreign policy strategy, significant influence came from the theoretical concepts and practices of the Indian independence movement, the oldest anti-colonial movement in the world. Tito’s visit to India and Burma in late 1954 and early 1955 was of great importance for strengthening cooperation, further emphasized by the fact that Tito was the first head of a European state to visit India after it gained independence. Following Broz’s visit to India and Burma in late 1954 and early 1955, economic cooperation between the two countries intensified. In July 1956, Nehru visited Yugoslavia once again, and during their meeting on the Brijuni Islands, Tito, Egyptian President Nasser, and Nehru adopted the Brijuni Declaration. However, the first international event that put Yugoslav-Indian relations to the test was the Hungarian Revolution of 1956.